Immunohistochemical demonstration of the binding of bothrops asper myotoxin to skeletal muscle sarcolemma - Brenes Pino, Fernando (1987)
The binding of Bothrops asper myotoxin to mouse skeletal muscle was studied at both the light and electron microscope levels using the peroxidase anti-peroxidase technique. The toxin binds to muscle cell sarcolemma, and there are no intracellular binding sites. This study corroborates previous observations which suggested that the sarcolemma is the first site of action of B. asper myotoxin.